Antenatal, intranatal and postnatal care: a tertiary centre study of North India - Gupta, Anjali; Khanna, Anish; Sachan, Rekha; Singh, V. K.; Singh, O. P. (International Journal Of Community Medicine And Public Health, 2018)
Background:Care of pregnant lady during antenatal period is the key to reducing maternal mortality and morbidity during pregnancy and child birth and futher improving the growth and development of the newborn. Optimal weight gain in the initial 6 months is very essential. Therefore, study aims to assess antenatal, intranatal and postnatal factors affecting the growth of newborn child. Methods:A Community based cross sectional study was conducted twice – at delivery and second after 6 months. A total of 220 ladies delivered at QMH, King Georges Medical University, Lucknow between August-2016 to September-2017 were included. WHO Standards were used to calculate the deviation from normal growth. Data was entered in SPSS-23 and assessment was made for factors affecting the growth of newborn. Results:At the time of birth the weight, length and head circumference of newborn was measured. Normal weight, length and H.C of ±2 SD was seen in 91%, 88%, 94% males respectively and 87.8%, 97.8 and 73.3% females. Repeat measurements at 6 month age of newborn showed normal weight, length and H.C in 62%, 58% and 87% males respectively and 87.8%, 74.4% and 96.7% females. Multivariate logistic regression analysis of factors revealed that growth of newborn upto 6 months was significantly associated with exclusive breastfeeding (OR 0.161; 95% CI 0.053-0.492; p=0.001), Illness in past 6 months (OR 6.820; 95%CI 2.376-19.579; p<0.001) low birth weight (OR 0.101; 95% CI 0.015-0.665; p=0.017). Conclusions:Although adherence to the proper schedule of antenatal, intranatal and postnatal visits and care varies between individuals and over time, the factors can be addressed with periodic counselling and motivation of pregnant ladies and their families.